Signatures of adaptation in human invasive Salmonella Typhimurium ST313 populations from sub-Saharan Africa. - Chinyere K Okoro; Lars Barquist; Thomas R Connor; Simon R Harris; Simon Clare; Mark P Stevens; Mark J Arends; Christine Hale; Leanne Kane; Derek J Pickard; Jennifer Hill; Katherine Harcourt; et al. (Public Library of Science (PLoS), 2015)
Two lineages of Salmonella enterica serovar Typhimurium (S. Typhimurium) of multi-locus sequence type ST313 have been linked with the emergence of invasive Salmonella disease across sub-Saharan Africa. The expansion of these lineages has a temporal association with the HIV pandemic and antibiotic usage. We analysed the whole genome sequence of 129 ST313 isolates representative of the two lineages and found evidence of lineage-specific genome degradation, with some similarities to that observed in S. Typhi. Individual ST313 S. Typhimurium isolates exhibit a distinct metabolic signature and modified enteropathogenesis in both a murine and cattle model of colitis, compared to S. Typhimurium outside of the ST313 lineages. These data define phenotypes that distinguish ST313 isolates from other S. Typhimurium and may represent adaptation to a distinct pathogenesis and lifestyle linked to an-immuno-compromised human population.